ENVIRONMENTAL AWARENESS OF PEOPLE AT DIFFERENT OCCUPATIONAL LEVELS: A CASE STUDY ON THE FARMERS, HOSPITAL AND INDUSTRIAL WORKERS, BANGLADESH - Shamim Al Mamun; Tanmoy Roy Tusher; Muliadi Muliadi; Muhammad Sirajul Islam; Asm Saifullah (Hasanuddin University, 2017)
The study was conducted to find out the level of environmental awareness of the farmers, hospital and industrial workers at Tangail Sadar Upazila in Tangail District, Bangladesh. The study included a questionnaire survey on a total of 390 respondents including 130 farmers, 130 hospital workers and 130 industrial workers in relation to their perception and awareness about several global and local environmental issues. Among the respondents 48.4% farmers were illiterate while all of the hospital and industrial workers passed the minimum level of education i.e. primary level. Only 12.1% and 6.6% of the hospital and industrial workers, respectively, completed their graduation whereas no farmer was found who completed the graduation. The study showed that the extent of environmental awareness varies among people at different occupational levels. The level of environmental awareness among the hospital workers was quite satisfactory than other groups of respondents. Industrial workers have comparatively better idea as their level of education was quite better than the farmers. Moreover, 33.6%, 58.2% and 35.6% of the farmers, hospital and industrial workers, respectively, participated in different awareness rising programs. The result of the study depicted that the hospital workers are much more conscious about different environmental issues than the others as their educational background was comparatively higher and also as they have participated comparatively in large number of environmental programs.